New Dawn or Bad Moon Rising? Large Scale Government Administered Workplace Surveys and the Future of Canadian IR Research - Godard, John (Relations industrielles / Industrial Relations, 2001)
SummaryThis article discusses the potential advantages of large scale, government administered workplace surveys and the limitations of these surveys in the past. It then reviews the 1995 AWIRS (Australia), the 1998 WERS (U.K.), and the 1999 WES (Canada) in accordance with how well they appear to have succeeded in overcoming these limitations, and, more generally, with their implications for the conduct of industrial relations (IR) research. It is argued that the 1995 AWIRS does not appreciably overcome the limitations of previous surveys. In contrast, the 1998 WERS has yielded a substantially higher quality data set, although it also does not completely overcome the limitations of its predecessors. Finally, the 1999 WES promises an even higher quality data set, but is primarily a labour market and productivity survey rather than an IR survey, and could even portend a “bad moon rising” for Canadian IR research.